Strategi Berbasis Komunitas dalam Pengelolaan Sub Daerah Aliran Sungai (Sub-DAS) Pusur di Kabupaten Klaten - Yuanita Dwi Hapsari; Deni Aries Kurniawan; Ghina Reftantia; Lisya Septiani Putri; Mallia Hartani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Community-based programs and activities aimed at watershed management have been widely promoted and implemented. Social control within the community plays a crucial role in regulating and transforming public behavior in managing rivers. This study aims to explore the strategies employed by community groups in managing the Pusur Sub-Watershed. This research uses a qualitative method with data collected through observation, interviews, and documentation. The results show that the strategies used by the community in managing the Pusur Sub-Watershed include the establishment of conservation field schools through both vegetative methods and the formation of plant cultivation groups in the upstream areas; the Clean River Program (Program Kali Bersih or Prokasih) through optimized waste management via Waste Banks; the River Care Program through the development of river tubing tourism in the midstream area of the Pusur River; environmentally friendly agriculture through agricultural clinics; irrigation management in the downstream area through the formation of the Combined Association of Water-User Farmers (Gabungan Perkumpulan Petani Pemakai Air or GP3A); and the emergence of collective actions in managing the Pusur Sub-Watershed through the establishment of the Pusur Institute.